Method for manufacturing Anti-reflection film

By using a specific protective film and real-time detection of reflected and transmitted light in the manufacturing process of the anti-reflective film, the problem of low detection accuracy in the prior art is solved, and higher detection accuracy and characteristic control are achieved.

CN119116492APending Publication Date: 2024-12-13NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410723006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-06-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to accurately measure the characteristics of reflected light and transmitted light in the online inspection of the anti-reflection film, especially on the formation surface side of the anti-reflection layer, resulting in low detection accuracy.

Method used

Using a protective film with specific surface haze values ​​and root mean square slope, the anti-reflection layer is formed on the transparent film substrate, and the reflected light and transmitted light are detected in real time during the film formation process, and the film formation conditions are adjusted to improve the detection accuracy. .

Benefits of technology

The accuracy of reflected light and transmitted light detection during online inspection is improved, the impact of back reflection is reduced, and the accuracy of control of the anti-reflection layer characteristics is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116492A_ABST
    Figure CN119116492A_ABST
Patent Text Reader

Abstract

The invention provides a method for manufacturing an anti-reflection film, which can improve the detection precision of reflected light and transmitted light during on-line inspection. A method for manufacturing an antireflection film (100) includes a step S1, a step S2, and a step S3. In step S1, a laminate (10) is prepared, the laminate (10) having a transparent film substrate (11) and a protective film (12) that is peelably bonded to a first main surface (11a) side of the transparent film substrate (11). In the step S2, an antireflection layer (101) comprising two or more thin films is formed on the second main surface (11b) side of the transparent film substrate (11). In step S3, at least one layer constituting the anti-reflection layer (101) is formed into a film, and then the film is irradiated with visible light, and reflected light and transmitted light thereof are detected. The step S2 and the step S3 are continuously performed while conveying the laminate (10) in one direction. The protective film (12) has an internal haze value of 4.0% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an antireflection film. Background Art

[0002] An anti-reflection film is arranged on the visible side of image display devices such as liquid crystal displays and organic EL displays to prevent image quality degradation caused by reflection of outdoor light and to improve contrast. The anti-reflection film has an anti-reflection layer composed of a laminate of multiple thin films with different refractive indices on a transparent film substrate.

[0003] The anti-reflection layer uses the multiple reflection interference of the film to reduce the reflectivity of visible light. Therefore, if the refractive index and film thickness of the film change, the reflected light characteristics such as reflectivity and hue of the reflected light will change. In the formation of the anti-reflection layer, even if the film forming conditions of the film are strictly managed and kept constant, the film thickness, refractive index, etc. of the film may change due to uneven properties of the raw materials, changes in the film forming environment over time, etc.

[0004] In film manufacturing, the following process is performed: online measurement is performed in the manufacturing process, and the measurement results are fed back to the previous process, thereby maintaining the quality of the film constant. For example, in Patent Document 1, as an online inspection in the manufacturing process of an anti-reflection film, the reflected light characteristics are measured online, and the measurement results are fed back to the film forming conditions of the thin film.

[0005] Generally, the anti-reflection film is designed so that the visible light reflectance of the anti-reflection layer forming surface is less than 1%. In contrast, the visible light reflectance (back reflectance) of the back side of the transparent film substrate (the interface between the transparent film substrate and the air) is about 4%. In the offline inspection after the anti-reflection layer is formed, the influence of the back reflection can be eliminated and the reflected light characteristics on the surface side can be measured. On the other hand, the reflected light detected by the online inspection in the manufacturing process of the anti-reflection film is mostly reflected light from the back side. Even if the characteristics of the reflected light from the anti-reflection layer forming surface change, the detected reflected light hardly changes. Therefore, it is usually not easy to accurately measure the characteristics of the reflected light from the anti-reflection layer forming surface online.

[0006] In contrast, according to the technology described in Patent Document 1, by forming an antireflection layer on a laminate having a light-diffusing adhesive layer, it is possible to reduce back reflection and improve the detection accuracy of reflected light during in-line inspection.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2016 / 021733

[0010] On the other hand, when the anti-reflection layer is continuously formed, the anti-reflection layer may be colored due to changes in film forming conditions, etc. In particular, when the anti-reflection layer is formed by reactive sputtering, it is difficult to stably maintain the transition region between the metal region and the oxide region, so the anti-reflection layer is easily colored.

[0011] As a method for sensing the coloration of the anti-reflection layer by online inspection, the following method can be cited: measuring the transmitted light characteristics of the anti-reflection layer and feeding back the measurement results to the film forming conditions of the thin film. However, it is not easy to improve the detection accuracy of the transmitted light during online inspection only by the technology described in Patent Document 1. Summary of the invention

[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for producing an antireflection film capable of improving the detection accuracy of reflected light and transmitted light during in-line inspection.

[0013] <Aspects of the present invention>

[0014] The present invention includes the following aspects.

[0015] [1] A method for manufacturing an antireflection film, comprising: step S1, preparing a laminate having a transparent film substrate and a protective film that is releasably attached to a first main surface side of the transparent film substrate; step S2, forming an antireflection layer composed of two or more thin films on a second main surface side of the transparent film substrate; and step S3, after forming at least one layer constituting the antireflection layer, irradiating the layer with visible light and detecting reflected light and transmitted light thereof, wherein steps S2 and S3 are continuously performed while conveying the laminate in one direction, wherein the internal haze value of the protective film is less than 4.0%, and the surface haze value of the main surface of the protective film on the side opposite to the transparent film substrate side is greater than 6.0% and less than 50.0%.

[0016] [2] The method for producing an antireflection film according to [1], wherein the value obtained by subtracting the surface haze value of the main surface of the protective film on the transparent film substrate side from the surface haze value of the main surface of the protective film on the opposite side to the transparent film substrate side is 5.0% or more.

[0017] [3] A method for manufacturing an antireflection film, comprising: step S1, preparing a laminate having a transparent film substrate and a protective film that can be peelably attached to a first main surface side of the transparent film substrate; step S2, forming an antireflection layer composed of two or more thin films on a second main surface side of the transparent film substrate; and step S3, after forming at least one layer constituting the antireflection layer, irradiating the layer with visible light and detecting its reflected light and transmitted light, wherein steps S2 and S3 are continuously performed while conveying the laminate in one direction, the internal haze value of the protective film is less than 4.0%, and the root mean square slope Sdq of the main surface of the protective film on the side opposite to the transparent film substrate is greater than 0.10 and less than 0.50.

[0018] [4] A method for manufacturing an anti-reflection film according to [3], wherein the value obtained by subtracting the root mean square slope Sdq of the main surface of the protective film on the side opposite to the transparent film substrate from the root mean square slope Sdq of the main surface of the protective film on the side of the transparent film substrate is greater than 0.05.

[0019] [5] The method for producing an antireflection film according to any one of [1] to [4], wherein in the step S2, the antireflection layer is formed by a reactive sputtering method.

[0020] [6] A method for producing an antireflection film according to any one of [1] to [5], wherein in step S3, after forming all the layers constituting the antireflection layer, the antireflection layer is irradiated with visible light, and its reflected light and transmitted light are detected.

[0021] [7] A method for manufacturing an anti-reflection film according to any one of [1] to [6], wherein the film forming conditions of the anti-reflection layer in the step S2 are adjusted based on the detection results of the reflected light and the transmitted light in the step S3.

[0022] [8] The method for producing an antireflection film according to any one of [1] to [7], further comprising: step S4 of peeling the protective film from the transparent film substrate after step S3.

[0023] [9] A method for producing an antireflection film according to any one of [1] to [8], wherein the transparent film substrate comprises a transparent film and a hard coating layer provided on a first main surface side of the transparent film, and in the laminate, the protective film is bonded to a second main surface side of the transparent film.

[0024]

[10] A method for manufacturing an anti-reflection film according to any one of [1] to [9], further comprising: step S5, before step S2, forming a primer layer on the second main surface side of the transparent film substrate, and in step S2, forming the anti-reflection layer on the main surface of the primer layer on the opposite side of the transparent film substrate.

[0025] Effects of the Invention

[0026] According to the present invention, it is possible to provide a method for producing an antireflection film capable of improving the detection accuracy of reflected light and transmitted light during in-line inspection. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a cross-sectional view showing an example of a laminate having a transparent film substrate and a protective film.

[0028] Figure 2 It is a schematic diagram showing an example of a film-forming apparatus for an antireflection layer.

[0029] Figure 3 A. Figure 3 B and Figure 3 C is a cross-sectional view divided into each step and showing an example of an anti-reflection layer forming step.

[0030] Description of Reference Numerals

[0031] 10: laminate; 11: transparent film substrate; 12: protective film; 13: transparent film; 14: hard coating layer; 100: antireflection film; 101: antireflection layer. DETAILED DESCRIPTION

[0032] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited thereto. In addition, all academic documents and patent documents described in this specification are cited in this specification as references.

[0033] First, the terms used in this specification are explained. "Refractive index" is the refractive index of light of wavelength 550nm in an atmosphere at a temperature of 23°C. The "principal surface" of a layered object (more specifically, a transparent film substrate, a transparent film, a hard coating layer, a primer layer, an antireflection layer, a protective film, a substrate layer, an adhesive layer, a laminate, etc.) refers to the surface of the layered object that is orthogonal to the thickness direction. The "first principal surface" of a layered object refers to one of the two principal surfaces of the layered object. The "second principal surface" of a layered object refers to the principal surface of the layered object on the side opposite to the first principal surface.

[0034] If there is no specification for the numerical value of the "thickness (film thickness)" of a layered material, it is obtained by observing a cross-section of the layered material cut along the thickness direction using an electron microscope, randomly selecting 10 measurement locations from the cross-section image, and measuring the thickness of the 10 selected measurement locations, and the arithmetic mean of the 10 measurement values ​​obtained.

[0035] "Root mean square slope Sdq" is a parameter of the surface shape measured according to ISO 25178, which indicates the degree of inclination of the convex part existing on the surface. "Arithmetic mean height Sa (surface roughness Sa)" is a parameter of the surface shape measured according to ISO 25178, which indicates the average of the absolute value of the difference between the height of each point and the average surface of the surface. "Root mean square height Sq" is a parameter of the surface shape measured according to ISO25178, which is equivalent to the standard deviation of the height from the average surface of the surface. The specific measurement methods of the root mean square slope Sdq, the arithmetic mean height Sa and the root mean square height Sq are the same as those in the embodiments described below or methods based on them.

[0036] The "bombard treatment" refers to a surface treatment in which a surface of a transparent film substrate is subjected to a plasma treatment while a predetermined gas (such as a rare gas or oxygen) is introduced.

[0037] Unless otherwise specified, the number average primary particle size of particles is the number average value of the projected area equivalent diameter (Heywood diameter: the diameter of a circle having the same area as the projected area of ​​the primary particles) of 100 primary particles measured using a scanning electron microscope and image processing software (e.g., "ImageJ" manufactured by the National Institutes of Health).

[0038] The unit of flow rate “sccm (Standard Cubic Centimeter per Minute)” is the unit of flow rate “mL / min” under standard conditions (temperature: 0° C., pressure: 101.3 kPa).

[0039] The “parallel line transmittance” is calculated by measuring the total light transmittance and diffuse transmittance based on the formula “parallel line transmittance = total light transmittance - diffuse transmittance”. The total light transmittance and diffuse transmittance are measured using a haze meter according to the method described in JIS K7105 (now abolished) (ISO 13468-2:1999).

[0040] Hereinafter, sometimes the suffix “-based” is added after the compound name to collectively refer to the compound and its derivatives. In addition, when the suffix “-based” is added after the compound name to indicate a polymer name, unless otherwise specified, it means that the repeating unit of the polymer is derived from the compound or its derivatives. In addition, acrylic acid and methacrylic acid are sometimes collectively referred to as “(meth)acrylic acid”.

[0041] As long as there is no special description, the components, functional groups, etc. exemplified in this specification can be used alone or in combination of two or more.

[0042] For easy understanding, the constituent elements of the drawings referred to in the following description are schematically shown in the main body. The size, number, shape, etc. of each constituent element shown in the drawings may sometimes be different from the actual ones for the convenience of drawing the drawings. In addition, for the convenience of explanation, in the drawings described later, the same constituent parts as those in the drawings described previously are given the same reference numerals and their descriptions are omitted.

[0043] <Manufacturing Method of Anti-Reflection Film>

[0044] The first manufacturing method of the anti-reflection film of this embodiment (hereinafter, sometimes referred to as “the first manufacturing method”) includes process S1, process S2, and process S3. In process S1, a laminate is prepared, which has a transparent film substrate and a protective film that can be peelably attached to the first main surface side of the transparent film substrate. In process S2, an anti-reflection layer composed of two or more thin films is formed on the second main surface side of the transparent film substrate. In process S3, after forming at least one layer constituting the anti-reflection layer, visible light is irradiated onto this layer, and its reflected light and transmitted light are detected. Process S2 and process S3 are continuously carried out while conveying the laminate in one direction. The internal haze value of the protective film used in the first manufacturing method is 4.0% or less. The surface haze value of the main surface of the protective film opposite to the transparent film substrate side used in the first manufacturing method is 6.0% or more and 50.0% or less.

[0045] The second manufacturing method of the anti-reflection film of the present embodiment (hereinafter sometimes described as "the second manufacturing method") includes steps S1, S2 and S3. In step S1, a laminate is prepared, which has a transparent film substrate and a protective film that can be peelably attached to the first main surface side of the transparent film substrate. In step S2, an anti-reflection layer composed of two or more thin films is formed on the second main surface side of the transparent film substrate. In step S3, after forming at least one layer constituting the anti-reflection layer, the layer is irradiated with visible light, and its reflected light and transmitted light are detected. Steps S2 and S3 are continuously implemented while conveying the laminate in one direction. The internal haze value of the protective film used in the second manufacturing method is less than 4.0%. The root mean square slope Sdq of the main surface of the protective film used in the second manufacturing method on the side opposite to the transparent film substrate side is greater than 0.10 and less than 0.50.

[0046] The method for measuring the "internal haze value" is the same method as the method for measuring the internal haze value of the protective films P1 to P3 described later or a method based thereon. The method for measuring the "surface haze value (external haze value)" is the same method as the method for measuring the surface haze value of the protective films P1 to P3 described later or a method based thereon.

[0047] Hereinafter, when no distinction is necessary, the first manufacturing method and the second manufacturing method are each described as “the present manufacturing method”. In addition, “the main surface of the protective film on the side opposite to the transparent film substrate side” may be simply described as “back surface”. In addition, “the main surface of the protective film on the transparent film substrate side” may be simply described as “adhesive surface”.

[0048] Hereinafter, step S1 may be described as a “laminated body preparation step.” Also, step S2 may be described as an “antireflection layer formation step.” Also, step S3 may be described as an “online measurement step.”

[0049] According to the manufacturing method, since the above-mentioned structure is provided, the detection accuracy of reflected light and transmitted light during in-line inspection can be improved. The reason is presumably as follows.

[0050] In the present manufacturing method, the anti-reflection layer is formed in a state where a protective film having a "surface haze value of 6.0% or more on the back side" or a "root mean square slope Sdq of 0.10 or more on the back side" is attached to a transparent film substrate, so there is a tendency that light incident from the anti-reflection layer side is easily scattered on the back side (rear side) of the protective film. As a result, the amount of light reflected on the back side (specifically, the reflected light reflected on the back side and detected by the light detection unit) (back side reflectivity) is reduced, so according to the present manufacturing method, the detection accuracy of the reflected light from the anti-reflection layer formation surface can be improved during online inspection.

[0051] In addition, in the present manufacturing method, the anti-reflection layer is formed in a state where a protective film having a "surface haze value of 50.0% or less on the back side" or a "root mean square slope Sdq of 0.50 or less on the back side" and an "internal haze value of 4.0% or less" is attached to a transparent film substrate. Therefore, according to the present manufacturing method, the proportion of parallel components of light incident from the anti-reflection layer side and emitted from the back side can be increased (parallel line transmittance is increased). Therefore, according to the present manufacturing method, the detection accuracy of light (transmitted light) that passes through the anti-reflection layer and is emitted from the back side can be improved during online inspection.

[0052] In the present manufacturing method, in order to further improve the detection accuracy of transmitted light, the internal haze value of the protective film is preferably 3.5% or less, and more preferably 3.0% or less. In addition, in the present manufacturing method, in order to further improve the detection accuracy of reflected light, the internal haze value of the protective film is preferably 0.5% or more, and more preferably 1.0% or more.

[0053] In the first manufacturing method, in order to further improve the detection accuracy of reflected light, the surface haze value of the back side of the protective film is preferably 6.1% or more, more preferably 6.2% or more. In addition, in the first manufacturing method, in order to further improve the detection accuracy of transmitted light, the surface haze value of the back side of the protective film is preferably 45.0% or less, more preferably 43.0% or less.

[0054] In the second manufacturing method, in order to further improve the detection accuracy of reflected light, the root mean square slope Sdq of the back side of the protective film is preferably 0.11 or more, and more preferably 0.12 or more. In addition, in the second manufacturing method, in order to further improve the detection accuracy of transmitted light, the root mean square slope Sdq of the back side of the protective film is preferably 0.45 or less, more preferably 0.40 or less, and further preferably 0.35 or less.

[0055] Hereinafter, the details of the method for producing an antireflection film according to the present embodiment (the present production method) will be described with reference to the drawings as appropriate.

[0056] [Laminate preparation step]

[0057] The laminate preparation step is a step of preparing a laminate having a transparent film substrate and a protective film attached to the first main surface of the transparent film substrate in a releasable manner. Figure 1 The laminated body will be described. Figure 1 It is a cross-sectional view showing an example of a laminated body.

[0058] Figure 1 The laminated body 10 shown in the figure comprises a transparent film substrate 11 and a protective film 12 which is bonded to a first main surface 11a of the transparent film substrate 11 in a releasable manner. The second main surface 11b of the transparent film substrate 11 is provided with an antireflection layer 101 (see Figure 3C) formation.

[0059] exist Figure 1 In the example shown, the transparent film substrate 11 includes a transparent film 13 and a hard coating layer 14 provided on the first main surface 13a side of the transparent film 13. Figure 1 In the example shown, the protective film 12 includes a substrate layer 15 and an adhesive layer 16 laminated on the transparent film substrate 11 side of the substrate layer 15. In addition, the protective film 12 is bonded to the second main surface 13b side of the transparent film 13. That is, the second main surface 13b of the transparent film 13 is bonded to the adhesive surface 12b of the protective film 12. Figure 1 In the example shown, the first principal surface 11 a of the transparent film substrate 11 and the second principal surface 13 b of the transparent film 13 are flush with each other.

[0060] In order to further improve the detection accuracy of the transmitted light, the total light transmittance (JIS K 7375-2008) of the protective film 12 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more.

[0061] It should be noted that in Figure 1 In the example shown, the transparent film substrate has a hard coating layer, but the transparent film substrate that can be used in the present invention is not limited to the above example. For example, the transparent film substrate that can be used in the present invention may not have a hard coating layer. In the case where the transparent film substrate does not have a hard coating layer, as the transparent film substrate, for example, a transparent film (in Figure 1 In the example shown, this is a transparent film 13 ).

[0062] In the present manufacturing method, the internal haze value of the protective film 12 is 4.0% or less. In the first manufacturing method, the surface haze value of the back surface 12a of the protective film 12 is 6.0% or more and 50.0% or less. In the second manufacturing method, the root mean square slope Sdq of the back surface 12a of the protective film 12 is 0.10 or more and 0.50 or less.

[0063] In the first manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the value obtained by subtracting the surface haze value of the adhesive surface 12b of the protective film 12 from the surface haze value of the back surface 12a of the protective film 12 is preferably 5.0% or more, and more preferably 5.5% or more. In the first manufacturing method, the upper limit of the value obtained by subtracting the surface haze value of the adhesive surface 12b of the protective film 12 from the surface haze value of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 40.0% or less.

[0064] In the second manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the value obtained by subtracting the root mean square slope Sdq of the adhesive surface 12b of the protective film 12 from the root mean square slope Sdq of the back surface 12a of the protective film 12 is preferably 0.05 or more, and more preferably 0.07 or more. In the second manufacturing method, the upper limit of the value obtained by subtracting the root mean square slope Sdq of the adhesive surface 12b of the protective film 12 from the root mean square slope Sdq of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 0.30 or less.

[0065] In the second manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the arithmetic mean height Sa of the back surface 12a of the protective film 12 is preferably 0.05 μm or more and 0.20 μm or less, and more preferably 0.06 μm or more and 0.18 μm or less. In addition, in the second manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the value obtained by subtracting the arithmetic mean height Sa of the adhesive surface 12b of the protective film 12 from the arithmetic mean height Sa of the back surface 12a of the protective film 12 is preferably 0.03 μm or more, and more preferably 0.04 μm or more. In the second manufacturing method, the upper limit of the value obtained by subtracting the arithmetic mean height Sa of the adhesive surface 12b of the protective film 12 from the arithmetic mean height Sa of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 0.20 μm or less.

[0066] In the second manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the root mean square height Sq of the back surface 12a of the protective film 12 is preferably 0.05 μm or more and 0.30 μm or less, and more preferably 0.07 μm or more and 0.25 μm or less. In addition, in the second manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the value obtained by subtracting the root mean square height Sq of the adhesive surface 12b of the protective film 12 from the root mean square height Sq of the back surface 12a of the protective film 12 is preferably 0.04 μm or more, and more preferably 0.05 μm or more. In the second manufacturing method, the upper limit of the value obtained by subtracting the root mean square height Sq of the adhesive surface 12b of the protective film 12 from the root mean square height Sq of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 0.25 μm or less.

[0067] The internal haze value of the protective film 12 can be adjusted by, for example, changing at least one of the content of particles in the protective film 12 and the particle size of particles in the protective film 12. In order to easily adjust the internal haze value of the protective film 12 to 4.0% or less, the content of particles in the protective film 12 is preferably 0.1% by weight or less, and more preferably, the protective film 12 contains substantially no particles.

[0068] The root mean square slope Sdq, the arithmetic mean height Sa and the root mean square height Sq of the surface of the protective film 12, and the surface haze value of the protective film 12 can be adjusted, for example, by changing the concavo-convex shape of the surface of the protective film 12. The concavo-convex shape of the surface of the protective film 12 is formed, for example, by using a roll forming machine having a forming roller with a concavo-convex surface to form the protective film 12. When a forming roller with a concavo-convex surface is used, the concavo-convex shape of the surface of the forming roller is transferred to the surface of the protective film 12 (for example, the back surface 12a of the protective film 12).

[0069] The laminate preparation step may be a step of preparing the laminate 10 as a commercial product, or a step of bonding the transparent film substrate 11 to the protective film 12. The method of bonding the transparent film substrate 11 to the protective film 12 is not particularly limited, and for example, the following method may be cited: using a roll-to-roll bonding device (not shown) to bond the protective film 12 to the first main surface 11a of the transparent film substrate 11 while conveying the transparent film substrate 11.

[0070] Next, each layer included in the laminate 10 will be described in detail.

[0071] (Transparent film 13)

[0072] The transparent film 13 is, for example, a flexible transparent resin film. As the material constituting the transparent film 13, for example, polyester resin, polyolefin resin, polystyrene resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyamide resin, polyimide resin, cellulose resin, norbornene resin, polyarylate resin and polyvinyl alcohol resin can be cited. As polyester resin, for example, polyethylene terephthalate (PET), polybutylene terephthalate and polyethylene naphthalate can be cited. As polyolefin resin, for example, polyethylene, polypropylene and cycloolefin polymer (COP) can be cited. As cellulose resin, for example, cellulose triacetate (TAC) can be cited. These materials can be used alone or in combination of two or more. As the material of the transparent film 13, from the viewpoint of transparency and strength, it is preferably selected from one of the group consisting of polyester resin, polyolefin resin and cellulose resin, more preferably selected from one of the group consisting of PET, COP and TAC, and further preferably TAC. That is, the transparent film 13 is preferably a film selected from the group consisting of polyester resin films, polyolefin resin films, and cellulose resin films, more preferably a film selected from the group consisting of PET films, COP films, and TAC films, and still more preferably a TAC film.

[0073] From the viewpoint of strength, the thickness of the transparent film 13 is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. From the viewpoint of handleability, the thickness of the transparent film 13 is preferably 300 μm or less, and more preferably 200 μm or less.

[0074] One or both main surfaces of the transparent film 13 may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.

[0075] From the viewpoint of improving the transparency of the antireflection film, the total light transmittance (JIS K7375-2008) of the transparent film 13 is preferably 80% or more, more preferably 90% or more, and further preferably 95% or more and 100% or less.

[0076] (Hard coating 14)

[0077] The hard coating layer 14 is a layer for improving the mechanical properties of the anti-reflection film, such as the hardness and elastic modulus. The hard coating layer 14 is composed of, for example, a cured product of a curable resin composition (composition for forming a hard coating layer). As the curable resin contained in the curable resin composition, for example, polyester resins, acrylic resins, carbamate resins, carbamate acrylate resins, amide resins, silicone resins, epoxy resins, and melamine resins can be cited. These curable resins can be used alone or in combination of two or more. From the viewpoint of improving the hardness of the hard coating layer 14, as the curable resin, it is preferably selected from one or more of the group consisting of acrylic resins and carbamate acrylate resins, and more preferably carbamate acrylate resins.

[0078] In addition, as a curable resin composition, for example, a UV-curable resin composition and a thermosetting resin composition can be listed. From the viewpoint of improving the productivity of the anti-reflection film, as a curable resin composition, a UV-curable resin composition is preferably used. The UV-curable resin composition includes one or more selected from the group consisting of a UV-curable monomer, a UV-curable oligomer, and a UV-curable polymer. As a specific example of a UV-curable resin composition, a hard coat forming composition described in Japanese Patent Publication No. 2016-179686 can be listed.

[0079] In addition, the curable resin composition may also contain particles having a number average primary particle size of 0.5 μm or more (hereinafter sometimes described as "micron particles"). That is, the hard coating layer 14 may also contain micron particles. By adding micron particles to the curable resin composition, the hardness, surface roughness, refractive index and anti-glare properties in the hard coating layer 14 can be adjusted. Examples of micron particles include metal (or semi-metal) oxide particles, glass particles and organic particles. Examples of materials for metal (or semi-metal) oxide particles include silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide and antimony oxide. Examples of materials for organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine and polycarbonate.

[0080] In order to easily adjust the anti-glare property of the hard coat layer 14 , the number average primary particle size of the micronized particles is preferably 1.0 μm or more and 5.0 μm or less, and more preferably 2.0 μm or more and 4.0 μm or less.

[0081] In order to easily adjust the anti-glare property of the hard coating layer 14, the amount of the micron particles in the hard coating layer 14 is preferably 5 parts by weight or more, and may be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more relative to 100 parts by weight of the curable resin. The upper limit of the amount of the micron particles in the hard coating layer 14 is, for example, 90 parts by weight, preferably 80 parts by weight, and may be 70 parts by weight relative to 100 parts by weight of the curable resin.

[0082] In addition, the curable resin composition may also include particles having a number average primary particle size of less than 0.5 μm (hereinafter, sometimes described as "nanoparticles"). When the hard coat layer 14 is composed of a cured product of a curable resin composition containing nanoparticles, fine concavoconvexities are formed on the surface of the hard coat layer 14, and there is a tendency for the hard coat layer 14 to have improved adhesion to the layer formed thereon.

[0083] From the viewpoint of forming fine concavo-convex shapes that contribute to improved adhesion, the number average primary particle size of the nanoparticles is preferably 20 nm to 80 nm, more preferably 25 nm to 70 nm, and even more preferably 30 nm to 60 nm.

[0084] As the material of the nanoparticles, inorganic oxides are preferred. Examples of inorganic oxides include oxides of metals (or semi-metals) such as silicon oxide (silicon dioxide), titanium oxide, aluminum oxide, zirconium oxide, niobium oxide, zinc oxide, tin oxide, cerium oxide, and magnesium oxide. The inorganic oxide may also be a composite oxide of multiple (semi) metals. Among the inorganic oxides exemplified, silicon oxide is preferred from the perspective of a high adhesion-enhancing effect. That is, as nanoparticles, silicon oxide particles (silicon dioxide particles) are preferred. On the surface of the inorganic oxide particles as nanoparticles, functional groups such as acryloyl and epoxy groups may also be introduced for the purpose of improving adhesion and affinity with the resin.

[0085] The amount of the nanoparticles in the hard coat 14 is preferably more than 5 parts by weight relative to 100 parts by weight of curable resin, and can also be more than 10 parts by weight, more than 20 parts by weight or more than 30 parts by weight. If the amount of the nanoparticles is more than 5 parts by weight, the adhesion with the layer formed on the hard coat 14 can be further improved. The upper limit of the amount of the nanoparticles in the hard coat 14 is, for example, 90 parts by weight relative to 100 parts by weight of curable resin, and is preferably 80 parts by weight, and can also be 70 parts by weight.

[0086] The curable resin composition (composition for forming a hard coat layer) comprises, for example, the above-mentioned curable resin and a polymerization initiator (e.g., a photopolymerization initiator), and, as required, a solvent capable of dissolving or dispersing these components. In addition, the curable resin composition (composition for forming a hard coat layer) may also comprise additives such as micron particles, nanoparticles, a leveling agent, a viscosity modifier (thixotropic agent, tackifier, etc.), an antistatic agent, an antiblocking agent, a dispersant, a dispersion stabilizer, an antioxidant, an ultraviolet absorber, a defoaming agent, a surfactant, and a lubricant in addition to the above-mentioned components.

[0087] From the viewpoint of increasing the hardness of the hard coating layer 14, the thickness of the hard coating layer 14 is preferably 1 μm or more, more preferably 2 μm or more. From the viewpoint of ensuring the flexibility of the anti-reflection film, the thickness of the hard coating layer 14 is preferably 50 μm or less, more preferably 40 μm or less, further preferably 35 μm or less, and further preferably 30 μm or less.

[0088] (Method for Forming Hard Coat Layer 14)

[0089] The hard coating layer 14 is formed, for example, by: Figure 1 In the embodiment, a curable resin composition (composition for forming a hard coat layer) is applied to the first main surface 13a of the transparent film 13, and the solvent is removed and the resin is cured as required. By providing a hard coat layer 14 on one main surface of the transparent film 13, as shown in FIG. Figure 1 As shown, a transparent film substrate 11 including a transparent film 13 and a hard coat layer 14 is obtained.

[0090] As a coating method for the hard coat forming composition, any appropriate method such as rod coating, roller coating, gravure coating, rod coating, slot orifice coating, curtain coating, fountain coating, comma coating, etc. can be adopted. The drying temperature of the coating film after coating can be set to an appropriate temperature according to the composition of the hard coat forming composition, for example, above 50°C and below 150°C. In the case where the resin component in the hard coat forming composition is a thermosetting resin, the coating film is cured by heating. In the case where the resin component in the hard coat forming composition is a photocurable resin, the coating film is cured by irradiating active energy rays such as ultraviolet rays. The cumulative light amount of the irradiated light is preferably 100mJ / cm 2 Above and 500mJ / cm 2 the following.

[0091] In order to improve the adhesion between the hard coating layer 14 and the layer formed thereon, the main surface of the hard coating layer 14 on the opposite side to the transparent film 13 side (on the Figure 1 In the embodiment, the bombardment treatment is performed on the second main surface 11b of the transparent film substrate 11. As the gas used in the bombardment treatment, one or more gases selected from the group consisting of rare gases (specifically, argon gas, etc.) and oxygen are preferably used.

[0092] In order to further improve the adhesion between the hard coat layer 14 and the layer formed thereon, the main surface of the hard coat layer 14 opposite to the transparent film 13 side is preferably subjected to a bombardment treatment under a pressure of 0.1 Pa to 1.0 Pa.

[0093] In order to further improve the adhesion between the hard coating layer 14 and the layer formed thereon, the effective power density in the bombardment treatment step is preferably 0.01 W·min / cm 2 ·m or more, more preferably 0.02W·min / cm 2 ·m or more, more preferably 0.03W·min / cm 2 In order to suppress the deformation of the transparent film substrate in the bombardment treatment process, the effective power density in the bombardment treatment process is preferably 0.60 W·min / cm 2 ·m or less, more preferably 0.55W·min / cm 2 ·m or less, more preferably 0.50W·min / cm 2 It should be noted that the effective power density refers to the power density (W / cm2 ) divided by the film conveying speed (m / min) of the roll-to-roll method. When the plasma output is the same but the conveying speed is increased, the effective processing power decreases.

[0094] (Base material layer 15)

[0095] The substrate layer 15 is formed of, for example, any appropriate film. As the constituent material of the film, for example, polyester resins such as polyethylene terephthalate resins, polycycloolefin resins such as polynorbornene resins, polyolefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof can be cited. In order to increase the hardness of the substrate layer 15, polyester resins are preferably used as the constituent material of the substrate. The thickness of the substrate layer 15 is, for example, not less than 10 μm and not more than 200 μm, preferably not less than 20 μm and not more than 150 μm. It should be noted that the substrate layer 15 may also be a laminate of two or more layers.

[0096] (Adhesive layer 16)

[0097] The adhesive layer 16 is formed of, for example, any appropriate adhesive (pressure-sensitive adhesive). Examples of the adhesive include (meth) acrylic adhesives, urethane adhesives, silicone adhesives, and the like. The thickness of the adhesive layer 16 is, for example, 1 μm to 20 μm, preferably 2 μm to 10 μm.

[0098] In order to improve the transportability of the laminate 10 , the total thickness of the base layer 15 and the adhesive layer 16 (the thickness of the protective film 12 ) is preferably 15 μm to 150 μm, and more preferably 20 μm to 100 μm.

[0099] [Anti-reflection layer forming step and online measuring step]

[0100] Next, refer to Figure 2 as well as Figure 3 A~ Figure 3 C, the anti-reflection layer forming process and the online measurement process are explained. Figure 2 It is a schematic diagram showing an example of a film-forming apparatus for an antireflection layer. Figure 3 A~ Figure 3 C is a cross-sectional view divided into each step and showing an example of an anti-reflection layer forming step.

[0101] First, an example of an apparatus for forming an antireflection layer will be described. Figure 2 The film forming apparatus shown is a film forming apparatus that can continuously perform an antireflection layer forming step and an inline measurement step while conveying a laminate in one direction, and can reflect the detection results in the inline measurement step on the film forming conditions of the antireflection layer forming step. Figure 2 The film forming device shown in the figure includes a first film forming roller 281 and a second film forming roller 282. Four film forming chambers (a first film forming chamber 210, a second film forming chamber 220, a third film forming chamber 230, and a fourth film forming chamber 240) divided by partition walls are provided along the circumferential direction of each film forming roller 281 and 282. A cathode is provided in each film forming chamber, and the cathodes 214, 224, 234, and 244 are connected to power supplies 216, 226, 236, and 246, respectively. On the cathodes 214, 224, 234, and 244, targets 213, 223, 233, and 243 are respectively arranged in a manner facing the film forming rollers 281 and 282. A gas introduction pipe is connected to each film forming chamber 210, 220, 230, and 240, and valves 219, 229, 239, and 249 are provided upstream of the gas introduction pipe.

[0102] The unwinding roll 251 in the preparation room 250 is loaded with the stacked body 10 (see Figure 3 The laminate 10 unwound from the unwinding roll 251 is transported to the first film-forming roll 281 and introduced into the first film-forming chamber 210 and the second film-forming chamber 220 in sequence. In the first film-forming chamber 210, the high refractive index layer 102 is formed on the side of the hard coating layer 14 opposite to the transparent film 13 (at Figure 3 In the A, the film is formed on the second main surface 11b of the transparent film substrate 11, and in the second film forming chamber 220, the low refractive index layer 103 is formed on the high refractive index layer 102 (refer to Figure 3 B). The laminate 10 on which the high refractive index layer 102 and the low refractive index layer 103 are formed is transported to the second film forming roller 282, and in the third film forming chamber 230 and the fourth film forming chamber 240, the high refractive index layer 104 and the low refractive index layer 105 are formed in sequence (refer to Figure 3 C). It should be noted that the details of the high refractive index layer and the low refractive index layer will be described later. Through the above anti-reflection layer forming step, the anti-reflection layer 101 having the high refractive index layer 102, the low refractive index layer 103, the high refractive index layer 104 and the low refractive index layer 105 in sequence is formed on the second main surface 11b of the transparent film substrate 11, Figure 3 The antireflection film 100 (laminated structure) shown in C.

[0103] The antireflection film 100 on which the antireflection layer 101 is formed is introduced into the winding chamber 260 and wound up by the winding roller 261 to obtain a rolled product of the antireflection film 100 .

[0104] In the winding chamber 260, a light irradiation section 291 and a light detection section 293 are arranged so as to face the anti-reflection layer 101 of the anti-reflection film 100. In addition, on the downstream side of the light irradiation section 291 and the light detection section 293, a light irradiation section 294 and a light detection section 295 are arranged so as to face each other with the anti-reflection film 100 sandwiched therebetween. In the online measurement process, the reflected light of the light irradiated from the light irradiation section 291 to the anti-reflection layer 101 is detected by the light detection section 293, and then the transmitted light of the light irradiated from the light irradiation section 294 to the anti-reflection layer 101 is detected by the light detection section 295. The light irradiated from the light irradiation section 291 and the light irradiation section 294 may be white light or monochromatic light as long as it includes visible light. The light irradiation may be performed continuously or intermittently.

[0105] The reflected light detected by the light detection unit 293 and the transmitted light detected by the light detection unit 295 are converted into electrical signals by light receiving elements (not shown) and are calculated by a computing unit (not shown) as needed. The computing unit calculates the spectrum of the detected reflected light and transmitted light, converts the spectrum into a specific colorimetric system (e.g., XYZ colorimetric system, L * a * b * color system, etc.), or calculation of film thickness, etc.

[0106] Furthermore, in the calculation unit, the difference between the reflection characteristics of the detected reflected light and the target reflection characteristics is determined, and the difference between the transmission characteristics of the detected transmitted light and the target transmitted light characteristics is determined. Then, when the difference exceeds the threshold, a signal is sent to the control unit 275 to change the film forming conditions of the thin film. The control unit 275 adjusts the film forming conditions of the anti-reflection layer 101 so that the characteristics of the reflected light (reflectivity, hue, etc.) and the characteristics of the transmitted light (spectral shape, etc.) are within the specified range.

[0107] The film forming conditions to be adjusted include the amount of gas introduced into the film forming chamber, the film transport speed, the input electrical energy, etc. Figure 2In the film forming apparatus shown, the control unit 275 can adjust the film forming conditions of the thin film in each film forming chamber by adjusting the rotation speed of the unwinding roller 251, the winding roller 261, the first film forming roller 281 and the second film forming roller 282; the input power of the power sources 216, 226, 236 and 246; and the opening of the valves 219, 229, 239 and 249 of the gas introduction pipe. For example, the change in the characteristics of the reflected light is mainly caused by the change in the film thickness of the film. Therefore, it is preferable to adjust the film forming conditions of the thin film in each film forming chamber in such a way that the film thickness of the thin film formed in each film forming chamber is close to the set value. In addition, the change in the characteristics of the transmitted light is mainly caused by the coloring of the thin film. Therefore, it is preferable to adjust the film forming conditions of the thin film in such a way as to suppress the coloring of the thin film formed in each film forming chamber. The adjustment of the film forming conditions is performed, for example, by PID control.

[0108] In order to determine the difference from the target reflected light characteristics and the target transmitted light characteristics, it is necessary to predetermine the reflected light characteristics and the transmitted light characteristics as a reference. The reflected light characteristics and the transmitted light characteristics as a reference are appropriately determined according to the specifications of the product, etc. As an example, there can be listed: a method of using the middle of the specification range of the product as a reference, and a method of using the reflected light spectrum calculated by optical calculation according to the set film thickness and refractive index of each layer (refer to the embodiment of Japanese Patent Gazette No. 2016-122173) as a reference. In addition, the reflected light spectrum and the transmitted light spectrum of the product measured offline can also be used as a reference.

[0109] In the present manufacturing method, as described above, the detection accuracy of reflected light and transmitted light during in-line inspection can be improved, so that the reflected light characteristics and transmitted light characteristics of the antireflection film can be easily controlled within the allowable range.

[0110] In order to suppress the unevenness of the reflected light characteristics in the width direction of the anti-reflection film, it is preferable to respectively set a plurality of light irradiation units 291 and light detection units 293 in the width direction of the anti-reflection layer 101, and perform online reflected light measurement (irradiation of visible light and detection of reflected light) at multiple locations in the width direction of the anti-reflection layer 101. Similarly, in order to suppress the unevenness of the transmitted light characteristics in the width direction of the anti-reflection film, it is preferable to respectively set a plurality of light irradiation units 294 and light detection units 295 in the width direction of the anti-reflection layer 101, and perform online transmitted light measurement (irradiation of visible light and detection of transmitted light) at multiple locations in the width direction of the anti-reflection layer 101. In this case, for example, if a plurality of gas introduction pipes are provided in each film forming chamber in the width direction of the film, the gas introduction amount can be adjusted at multiple locations in the width direction of the film.

[0111] When the anti-reflection layer 101 is formed by a reactive sputtering method, when adjusting the film forming conditions of the anti-reflection layer 101, it is preferred to control the amount of reactive gas such as oxygen by plasma emission monitoring (PEM) control. In PEM control, the plasma luminescence intensity of the sputtering film is sensed, and the amount of reactive gas introduced is adjusted in such a way that the luminescence intensity becomes a predetermined control value (set point, sometimes referred to as "SP" below). By automatically adjusting the amount of gas introduced in such a way that the plasma luminescence intensity becomes constant, the transition region can be maintained and the film can be formed at a high rate, and the film forming rate can be kept constant. However, if the film formation is continuously carried out for a long time, the film forming rate will change even if the plasma luminescence intensity is the same due to the influence of target corrosion, etc. Therefore, in the case of implementing long-term continuous film formation, in order to suppress the changes in the reflected light characteristics and the transmitted light characteristics in the long-dimensional direction of the anti-reflection film, it is preferred to appropriately adjust the SP of the PEM based on the measurement results of the optical characteristics in the online measurement process.

[0112] In PEM control, in order to control the state of sputtering film formation in each film forming chamber, the plasma luminous intensity is monitored at any time by PEM, and the amount of gas introduced into each film forming chamber is feedback controlled based on the SP set to the luminous intensity in a specified range. By providing a plurality of PEM control devices in the width direction of the film, the SP can be set separately in each PEM control device. In this way, the balance of the amount of gas introduced into the position in the width direction corresponding to the PEM control device can be adjusted, so that the anti-reflection layer 101 having a uniform film thickness in the width direction can be formed. For example, by detecting reflected light in an online measurement process, the film thickness is calculated based on the detection result, and the SP is changed in a manner that the film thickness of the anti-reflection layer 101 is uniform in the long dimension direction or the width direction of the film based on the calculation result, and the reflected light characteristics in the long dimension direction or the width direction of the film can be kept uniform.

[0113] Generally, when the anti-reflection layer is formed by reactive sputtering, it is difficult to stably maintain the transition region, so the anti-reflection layer is easily colored. As described above, in the present manufacturing method, the detection accuracy of the transmitted light can be improved, so the transmitted light characteristics of the anti-reflection layer can be easily controlled within the allowable range. Therefore, according to the present manufacturing method, even if the reactive sputtering method is used, the transmitted light characteristics of the anti-reflection layer can be easily controlled within the allowable range, so the coloring of the anti-reflection layer can be suppressed.

[0114] The present production method may further include step S4 of peeling the protective film 12 from the transparent film substrate 11 after the in-line measurement step. An optical layer such as a polarizing plate is laminated on the first main surface 11a of the transparent film substrate 11 after the protective film 12 is peeled off.

[0115] (Anti-reflection layer 101)

[0116] Next, the details of the antireflection layer 101 will be described. The antireflection layer 101 is composed of two or more thin films. Figure 3 The anti-reflection layer 101 shown in C has four layers of high refractive index layer 102, low refractive index layer 103, high refractive index layer 104 and low refractive index layer 105 in order from the hard coating layer 14 side. It should be noted that the anti-reflection layer of the anti-reflection film is not limited to the four-layer structure of the anti-reflection layer 101, and can also be a two-layer structure, a three-layer structure, a five-layer structure or a stacked structure of more than six layers. In order to reduce reflection at the air interface, the anti-reflection layer of the anti-reflection film preferably has a low refractive index layer as the outermost layer (the layer farthest from the transparent film substrate).

[0117] Generally, for an anti-reflection layer, the optical film thickness (product of refractive index and thickness) of the film is adjusted in such a way that the reverse phases of incident light and reflected light cancel each other out. By making the anti-reflection layer a multilayer stack of two or more thin films with different refractive indices, the reflectivity can be reduced within a wide wavelength range of visible light.

[0118] As the material of the thin film constituting the anti-reflection layer 101, there can be listed: metal (or semi-metal) oxides, nitrides, fluorides, etc. The anti-reflection layer 101 is preferably an alternating stack of high refractive index layers and low refractive index layers, and more preferably an alternating stack of two or more high refractive index layers and two or more low refractive index layers.

[0119] The refractive index of the high refractive index layer is, for example, 1.9 or more, preferably 2.0 or more. As the material of the high refractive index layer, there can be listed: titanium oxide, niobium oxide (Nb2O5, etc.), zirconium oxide, tantalum oxide, zinc oxide, indium oxide, indium tin oxide (ITO), antimony-doped tin oxide (ATO), etc. Among them, it is preferred to select one or more of the group consisting of titanium oxide and niobium oxide. The refractive index of the low refractive index layer is, for example, 1.6 or less, preferably 1.5 or less. As the material of the low refractive index layer, there can be listed: silicon oxide (SiO2, etc.), titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, lanthanum fluoride, etc. Among them, silicon oxide is preferred. It is particularly preferred to alternately stack a niobium oxide film as a high refractive index layer and a silicon oxide film as a low refractive index layer. In addition to providing a low refractive index layer and a high refractive index layer, a medium refractive index layer having a refractive index greater than 1.6 and less than 1.9 can also be provided.

[0120] The film thickness of high refractive index layer and low refractive index layer is preferably more than 5nm and less than 200nm respectively, more preferably more than 10nm and less than 150nm.As long as according to refractive index, stacking constitution etc., the film thickness of each layer is designed in a way that the reflectivity of visible light decreases.For example, as the stacking constitution of high refractive index layer and low refractive index layer, it is possible to list: from the transparent film substrate 11 side, a high refractive index layer including an optical film thickness of more than 20nm and less than 55nm, a low refractive index layer including an optical film thickness of more than 35nm and less than 60nm, a high refractive index layer including an optical film thickness of more than 65nm and less than 250nm, and a low refractive index layer including an optical film thickness of more than 100nm and less than 150nm has a four-layer constitution.

[0121] In the case where the anti-reflection layer 101 is a four-layer alternating stack of niobium oxide thin films as high refractive index layers and silicon oxide thin films as low refractive index layers, the composition of the anti-reflection layer 101 can be listed as follows: a niobium oxide thin film with a thickness of 5 nm to 20 nm, a silicon oxide thin film with a thickness of 20 nm to 60 nm, a niobium oxide thin film with a thickness of 25 nm to 120 nm, and a silicon oxide thin film with a thickness of 50 nm to 100 nm, in order from the hard coating layer 14 side.

[0122] In order to obtain an anti-reflection film with excellent high-temperature durability, the thickness of the anti-reflection layer 101 is preferably 100 nm or more and 300 nm or less, more preferably 120 nm or more and 280 nm or less, further preferably 140 nm or more and 260 nm or less, and further preferably 160 nm or more and 240 nm or less. It should be noted that in this specification, the "thickness of the anti-reflection layer" is the sum of the thicknesses of the layers constituting the anti-reflection layer (total thickness).

[0123] The film forming method of the anti-reflection layer 101 is not particularly limited, and may be any of a wet coating method and a dry coating method. From the perspective of being able to form a thin film with uniform film thickness, a dry coating method such as a vacuum evaporation method, a CVD method, a sputtering method, etc. is preferred, and a sputtering method is more preferred. From the perspective of improving productivity, as a film forming method of the anti-reflection layer 101, it is preferred to use a method such as Figure 2 A method of forming a film using a roll-to-roll sputtering film forming apparatus (roll-to-roll sputtering method). In the sputtering method, film formation is performed while an inert gas such as argon and a reactive gas such as oxygen introduced as needed are introduced into a film forming chamber. When an oxide film is formed by sputtering, any of a method using an oxide target and a reactive sputtering method using a metal (or semi-metal) target can be implemented.

[0124] When an oxide target is used to form an insulating oxide such as silicon oxide, RF discharge is required, so there is a tendency that the film forming rate is small and the productivity becomes low. Therefore, the sputtering film forming of the oxide preferably uses a reactive sputtering method using a metal target. In the reactive sputtering method, an inert gas such as argon and a reactive gas such as oxygen are introduced into the film forming chamber while film forming is performed. In the reactive sputtering method, the amount of oxygen is preferably adjusted in a manner that becomes a transition zone between the metal region and the oxide region. If film formation is performed in a metal region where the amount of oxygen is insufficient, the amount of oxygen in the obtained oxide film is greatly reduced compared to the stoichiometric composition, and there is a tendency that the oxide film has a metallic luster and reduced transparency. In addition, in an oxide region with a large amount of oxygen, there is a tendency that the film forming rate is extremely reduced. By adjusting the amount of oxygen in a manner that sputtering film forming becomes a transition zone, the oxide film can be formed at a high rate. In the case of forming the anti-reflection layer 101 by a reactive sputtering method, the amount of reactive gas introduced can be controlled by the above-mentioned PEM control, so that the adjustment of the film forming conditions of the anti-reflection layer 101 becomes easier. As a sputtering power source used in the reactive sputtering method, a DC power source or an MFAC power source (an AC power source having a frequency band of several kHz to several MHz) is preferable.

[0125] The power density when sputtering is performed is, for example, 0.1 W / cm 2 Above and 20W / cm 2 Below, preferably 1W / cm 2 Above and 15W / cm 2 The surface temperature of the deposition roller during sputtering is, for example, -25°C to 25°C, preferably -20°C to 0°C. The pressure in the deposition chamber during sputtering is, for example, 0.01 Pa to 10 Pa, preferably 0.1 Pa to 1.0 Pa.

[0126] The antireflection film obtained by the present production method is used in displays such as liquid crystal display devices and organic EL display devices. In particular, when used as the outermost layer of a display, the visibility of the display is improved by antireflection.

[0127] [Preferred embodiment of the method for producing an antireflection film]

[0128] In the present manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light during online inspection, it is preferred to satisfy the following condition 1, more preferred to satisfy the following condition 2, and even more preferred to satisfy the following condition 3.

[0129] Condition 1: The surface haze value of the back surface of the protective film is 6.0% or more and 50.0% or less, and the root mean square slope Sdq of the back surface of the protective film is 0.10 or more and 0.50 or less.

[0130] Condition 2: The above-mentioned condition 1 is satisfied, and the value obtained by subtracting the surface haze value of the adhesive surface of the protective film from the surface haze value of the back surface of the protective film is 5.0% or more.

[0131] Condition 3: The above-mentioned condition 2 is satisfied, and a value obtained by subtracting the root mean square slope Sdq of the adhesive surface of the protective film from the root mean square slope Sdq of the back surface of the protective film is 0.05 or more.

[0132] [Other embodiments]

[0133] The above is a description of the method for manufacturing the anti-reflection film of the present embodiment, but the present invention is not limited to the above embodiment. For example, the online measurement process can be performed at any stage as long as it is performed after at least one thin film is formed. For example, after the high refractive index layer 102 and the low refractive index layer 103 are formed on the first film-forming roller 281, the light irradiation unit 297 (see Figure 2 ) irradiates the low refractive index layer 103 with visible light, and the light detection unit 299 (refer to Figure 2 ) detects the reflected light, thereby performing online detection of the reflected light. In addition, after forming the high refractive index layer 102 and the low refractive index layer 103 on the first film-forming roller 281, visible light may be irradiated from a light irradiation unit (not shown) to the low refractive index layer 103, and the transmitted light may be detected by a light detection unit (not shown), thereby performing online detection of the transmitted light.

[0134] In addition, Figure 2 , an example of detecting the transmitted light after detecting the reflected light is shown in FIG. 1 , but in the present invention, the reflected light may be detected after detecting the transmitted light. In addition, the reflected light and the transmitted light may be detected simultaneously.

[0135] In addition, online detection may be performed at two or more locations. For example, after forming the high refractive index layer 102 and the low refractive index layer 103, online detection of reflected light and transmitted light may be performed, and further, after forming the high refractive index layer 104 and the low refractive index layer 105, online detection of reflected light and transmitted light may be performed. In this way, if online measurement is performed at two or more locations, it becomes easy to determine the film forming chamber where the film forming conditions should be adjusted, and more precise control can be performed.

[0136] In addition, the manufacturing method of the present invention may also include: step S5, before the anti-reflection layer forming step, forming a primer layer on one main surface (second main surface) side of the transparent film substrate. When the manufacturing method of the present invention also includes step S5, in the anti-reflection layer forming step, the anti-reflection layer is formed on the main surface of the primer layer on the opposite side of the transparent film substrate side.

[0137] By providing a primer layer, the adhesion between the transparent film substrate and the anti-reflection layer becomes higher. As materials for the primer layer, there can be listed: metals (or semi-metals) such as silicon, nickel, chromium, tin, gold, silver, platinum, zinc, titanium, indium, tungsten, aluminum, zirconium, palladium, etc.; alloys of these metals (or semi-metals); oxides, fluorides, sulfides or nitrides of these metals (or semi-metals), etc. The oxide constituting the primer layer can also be a composite oxide such as indium tin oxide (ITO). Among them, as the material of the primer layer, inorganic oxides are preferred, silicon oxide, indium oxide or ITO are more preferred, and SiOx (x<2) is further preferred.

[0138] In order to improve the adhesion between the transparent film substrate and the antireflection layer and ensure the light transmittance of the primer layer, the thickness of the primer layer is preferably 0.5 nm to 20 nm, more preferably 0.5 nm to 10 nm, and further preferably 1.0 nm to 10 nm.

[0139] The film-forming method of the primer layer is not particularly limited, and can be any of a wet coating method and a dry coating method. From the perspective of being able to form a thin film with uniform film thickness, dry coating methods such as vacuum evaporation, CVD, and sputtering are preferred, and sputtering is more preferred. From the viewpoint of improving productivity, as a film-forming method for the primer layer, a method (roll-to-roll sputtering method) of film-forming using a roll-to-roll sputtering film-forming device is preferred. In the roll-to-roll sputtering method, a long laminate can be transported in the long dimension direction (MD direction) while, for example, the primer layer and the anti-reflection layer can be continuously film-formed. When the primer layer is film-formed by sputtering, for example, the film-forming conditions can be appropriately set in the conditions exemplified in the description of the above-mentioned anti-reflection layer 101.

[0140] Furthermore, the method for producing an antireflection film of the present invention may include a step of forming an antifouling layer after the online measurement step. As a material for the antifouling layer, a fluorine-containing compound is preferred.

[0141] In the method for producing an antireflection film of the present invention, the protective film may be composed of only one layer (base layer). The protective film composed of only the base layer has, for example, adhesiveness on one main surface.

[0142] Example

[0143] Hereinafter, examples of laminates that can be used in the present invention and production examples of antireflection films using these laminates will be described.

[0144] <Production of laminate>

[0145] [Preparation of protective film]

[0146] As protective films for making laminates, protective films P1 to P7 shown in Table 1 were prepared. It should be noted that protective film P1 is composed of only a substrate layer (thickness: 28 μm) having adhesiveness on one main surface. In addition, protective films P2 to P7 all have a substrate layer and an adhesive layer. In addition, protective films P5 to P7 are light-diffusing adhesive layers in which the adhesive layer contains particles, and the content of particles in the light-diffusing adhesive layer is different.

[0147] [Table 1]

[0148]

[0149] [Formation of hard coat layer]

[0150] 100 parts by weight of ultraviolet curable urethane acrylate monomer (refractive index: 1.51), 14 parts by weight of polystyrene beads (refractive index: 1.59, number average primary particle size: 3.5 μm), 5 parts by weight of alkylphenone photopolymerization initiator, 135 parts by weight of toluene and 10 parts by weight of ethyl acetate were mixed to prepare a hard coating layer forming composition having a solid content concentration of 45% by weight. Next, the hard coating layer forming composition was applied to one main surface of a TAC film (thickness: 40 μm, refractive index: 1.49) as a transparent film to form a coating film. Next, the coating film was heated at a temperature of 80°C for 2 minutes to dry it, and then cured by ultraviolet irradiation. Thus, a 7 μm thick anti-glare hard coating layer (a hard coating layer having a concave-convex structure on the surface) was formed on one main surface of the TAC film, and a transparent film substrate was obtained.

[0151] [Attachment of protective film]

[0152] The main surface of the TAC film side of the transparent film substrate obtained by the above process is attached to the adhesive surface of the above-mentioned protective film (specifically, any of the protective films P1 to P7) to obtain a laminate. Hereinafter, the laminate obtained using the protective film P1 is sometimes described as "laminate L1". Similarly, the laminates obtained using the protective films P2, P3, P4, P5, P6 and P7 are sometimes described as "laminates L2, L3, L4, L5, L6 and L7", respectively.

[0153] <Production of anti-reflection film>

[0154] Hereinafter, the method for producing the antireflection films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4 will be described.

[0155] [Production Example 1]

[0156] (Bombardment treatment)

[0157] Using a roll-to-roll plasma processing device, the pressure is 0.6Pa and the effective power density is 0.34W·min / cm 2 Under the condition of ·m, the main surface of the hard coating layer of the laminate L1 (specifically, the main surface of the hard coating layer opposite to the TAC film side) was bombarded while conveying the laminate L1. During the bombardment, argon gas (flow rate: 1050 sccm) was introduced into the apparatus.

[0158] Next, the primer layer forming process and the anti-reflection layer forming process are described. It should be noted that in the primer layer forming process and the anti-reflection layer forming process, when the oxide film is formed (film formation), argon gas and oxygen are introduced into the film forming chamber while the film is formed. In addition, when the oxide film is formed (film formation), the pressure is kept constant by adjusting the introduction amount and exhaust amount of argon gas, and the introduction amount of oxygen is adjusted in a manner to maintain the transition zone in the film forming mode through plasma emission monitoring (PEM) control.

[0159] (Primer layer forming step)

[0160] The laminate L1 after the bombardment treatment was introduced into a roll-to-roll sputtering film forming apparatus, and the pressure in the film forming chamber was reduced to 1×10 -4 Pa. Then, while conveying the laminate L1, the surface temperature of the film-forming roller was kept at -8°C, and a SiOx layer (x < 2) with a thickness of 3.5 nm was formed (filmed) as a primer layer on the main surface of the hard coating layer opposite to the TAC film side by a reactive sputtering method. In the formation of the primer layer, a Si target was used as a target material. In addition, when forming the film by the reactive sputtering method, the power supply was set to an MFAC power supply (frequency: 40 kHz), and the power density was set to 3 W / cm 2 , and set the pressure in the film forming chamber to 0.4Pa.

[0161] (Anti-reflection layer forming step)

[0162] After the formation of the primer layer, a roll-to-roll sputtering film-forming device is used to transport the laminate L1 after the primer layer is formed, and at the same time, by a reactive sputtering method, the first layer: a 12nm thick niobium oxide layer (refractive index: 2.33), the second layer: a 28nm thick silicon oxide layer (refractive index: 1.46), the third layer: a 100nm thick niobium oxide layer, and the fourth layer: a 85nm thick silicon oxide layer are formed in sequence on the main surface of the primer layer on the opposite side of the hard coating layer. Thus, an anti-reflection layer consisting of four layers (consisting of the first layer, the second layer, the third layer and the fourth layer) is formed on one main surface of the primer layer, and the anti-reflection film of Manufacturing Example 1 is obtained. It should be noted that in the film formation of each of the first to fourth layers, the surface temperature of the film-forming roller was set to -8°C, and the power supply was set to an MFAC power supply (frequency: 40kHz). In addition, in the film formation of the first and third layers, Nb targets were used, and the power density was set to 13W / cm 2 , the pressure in the film forming chamber was set to 0.5 Pa. In addition, Si targets were used in the film formation of the second and fourth layers, and the power density was set to 8 W / cm 2 , and set the pressure in the film forming chamber to 0.5Pa.

[0163] [Manufacturing Example 2, Manufacturing Example 3, and Comparative Manufacturing Examples 1 to 4]

[0164] Antireflection films of Manufacturing Example 2, Manufacturing Example 3, and Comparative Manufacturing Examples 1 to 4 were obtained by the same method as in Example 1 except that the stacked bodies L2 to L7 were used respectively in place of the stacked body L1.

[0165] <Measurement of internal haze value>

[0166] [Measurement of internal haze value of protective films P1 to P4]

[0167] First, the adhesive surface of the protective film (specifically, any of the protective films P1 to P4) was bonded to one main surface of a glass slide having a thickness of 1.3 mm via an acrylic adhesive layer (thickness: 23 μm), and then a PET film (thickness: 38 μm) was bonded to the back of the protective film via an acrylic adhesive layer (thickness: 23 μm), thereby obtaining a laminate La. Separately, materials of the same type as those used to form the laminate La, the glass slide, the acrylic adhesive layer, and the PET film were used to obtain a laminate Lb having a layer structure of a glass slide (thickness: 1.3 mm) / acrylic adhesive layer (thickness: 46 μm) / PET film (thickness: 38 μm). Next, the haze values ​​of the laminates La and Lb were measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments) by the method described in JIS K7136-2000. Then, the internal haze value of the protective films P1 to P4 was obtained by subtracting the haze value of the laminate Lb from the haze value of the laminate La. In addition, when measuring the haze values ​​of the laminates La and Lb, light was irradiated from the PET film side.

[0168] [Measurement of internal haze value of protective films P5 to P7]

[0169] First, the adhesive surface of the protective film (specifically, any of the protective films P5 to P7) was bonded to one main surface of a glass slide having a thickness of 1.3 mm, and then a PET film (thickness: 38 μm) was bonded to the back of the protective film via an acrylic adhesive layer (thickness: 23 μm), thereby obtaining a laminate Lc. Separately, materials of the same type as those used to form the laminate Lc, the glass slide, the acrylic adhesive layer, and the PET film were used to obtain a laminate Ld having a layer structure of a glass slide (thickness: 1.3 mm) / acrylic adhesive layer (thickness: 23 μm) / PET film (thickness: 38 μm). Next, the haze values ​​of the laminates Lc and Ld were measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments) by the method described in JIS K7136-2000. Then, the value obtained by subtracting the haze value of the laminate Ld from the haze value of the laminate Lc was taken as the internal haze value of the protective films P5 to P7. In addition, when measuring the haze values ​​of the laminate Lc and the laminate Ld, light was irradiated from the PET film side.

[0170] <Measurement of surface haze value>

[0171] [Measurement of Surface Haze Value of Backside of Protective Films P1 to P4]

[0172] First, using the same type of materials as the glass slide and acrylic adhesive layer used when forming the laminate La, a laminate Le having a layer structure of a glass slide (thickness: 1.3 mm) / acrylic adhesive layer (thickness: 23 μm) / protective film (specifically, any one of the protective films P1 to P4) was obtained. It should be noted that when forming the laminate Le, the adhesive surface of the protective film was attached to the acrylic adhesive layer. Next, the haze value of the laminate Le was measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments) by the method described in JIS K7136-2000. Then, the value obtained by subtracting the internal haze value of the protective film (specifically, any one of the protective films P1 to P4) from the haze value of the laminate Le was used as the surface haze value of the back of the protective films P1 to P4. It should be noted that when measuring the haze value of the laminate Le, light was irradiated from the protective film side.

[0173] [Measurement of Surface Haze Value of Adhesive Surfaces of Protective Films P1 to P4]

[0174] First, using the same type of materials as the glass slide and acrylic adhesive layer used when forming the laminate La, a laminate Lf having a layer structure of a glass slide (thickness: 1.3 mm) / acrylic adhesive layer (thickness: 23 μm) / protective film (specifically, any one of the protective films P1 to P4) was obtained. It should be noted that when forming the laminate Lf, the back of the protective film was attached to the acrylic adhesive layer. Next, the haze value of the laminate Lf was measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments) by the method described in JIS K7136-2000. Then, the value obtained by subtracting the internal haze value of the protective film (specifically, any one of the protective films P1 to P4) from the haze value of the laminate Lf was used as the surface haze value of the bonding surface of the protective films P1 to P4. It should be noted that when measuring the haze value of the laminate Lf, light was irradiated from the protective film side.

[0175] [Measurement of Surface Haze Value of Backside of Protective Films P5 to P7]

[0176] First, the adhesive surface of the protective film (specifically, any one of the protective films P5 to P7) was attached to a slide glass (thickness: 1.3 mm) of the same type as the slide glass used when forming the laminate Lc, and the laminate Lg was obtained. Next, the haze value of the laminate Lg was measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments) by the method described in JIS K7136-2000. Then, the value obtained by subtracting the internal haze value of the protective film (specifically, any one of the protective films P5 to P7) from the haze value of the laminate Lg was used as the surface haze value of the back of the protective films P5 to P7. It should be noted that when the haze value of the laminate Lg is measured, light is irradiated from the protective film side.

[0177] <Measurement of surface shape of protective film>

[0178] Using a protective film (specifically, any one of the protective films P1 to P7) as a sample, a shape analysis laser microscope ("VK-X1000" manufactured by KEYENCE) is used to measure the three-dimensional surface shape of the surface of the protective film (specifically, any one of the back surface and the adhesive surface) under the following conditions. In accordance with ISO 25178, the root mean square slope Sdq, arithmetic mean height Sa, and root mean square height Sq are obtained.

[0179] Observation magnification: 150 times.

[0180] Measurement field of view: 50 μm × 50 μm.

[0181] <Measurement of back surface reflectivity of antireflection film>

[0182] First, an anti-reflection film FS was prepared as a reference sample. Specifically, when forming a laminate, an acrylic adhesive layer (thickness: 23 μm) and a black PET film (thickness: 50 μm, visible light transmittance: 0.1%) were sequentially laminated on the main surface of the TAC film side of the transparent film substrate instead of the protective film P1, and the anti-reflection film FS was prepared by the same method as the anti-reflection film of Manufacturing Example 1. The layer structure of the anti-reflection film FS is black PET film / acrylic adhesive layer / TAC film / hard coating layer / primer layer / anti-reflection layer. Next, regarding the anti-reflection film FS and the anti-reflection film to be measured (specifically, the anti-reflection film of Manufacturing Examples 1 to 3 and Comparative Manufacturing Examples 1 to 4), a UV-visible near-infrared spectrophotometer ("U4100" manufactured by Hitachi High-Tech Co., Ltd.) was used to irradiate visible light (wavelength: 550 nm) from the anti-reflection layer side under the condition of an incident angle of 2°, and the reflectivity (unit: %) of 2° regular reflection was measured. Then, the value obtained by subtracting the reflectivity of the anti-reflection film FS from the reflectivity of the anti-reflection film to be measured (specifically, any of the anti-reflection films of Manufacturing Examples 1 to 3 and Comparative Manufacturing Examples 1 to 4) is taken as the back reflectivity (unit: %) of the anti-reflection film to be measured. When the back reflectivity is 0.30% or less, it is evaluated as "back reflection is reduced". On the other hand, when the back reflectivity is greater than 0.30%, it is evaluated as "back reflection is not reduced".

[0183] <Measurement of Parallel Line Transmittance of Antireflection Film>

[0184] Regarding the antireflection film to be measured (specifically, the antireflection film of Manufacturing Examples 1 to 3 and Comparative Manufacturing Examples 1 to 4), a haze meter ("HZ-2" manufactured by Suga Test Instruments) was used to measure the total light transmittance (unit: %) and the diffuse transmittance (unit: %) when light was irradiated from the antireflection layer side by the method described in JIS K7105 (now abolished) (ISO 13468-2: 1999). Then, the parallel line transmittance (unit: %) of the antireflection film to be measured was calculated based on the formula "parallel line transmittance = total light transmittance - diffuse transmittance". When the parallel line transmittance is 30.0% or more, it is evaluated as "the parallel line transmittance is high". On the other hand, when the parallel line transmittance is less than 30.0%, it is evaluated as "the parallel line transmittance is not high".

[0185] <Results>

[0186] Regarding the antireflection films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4, the types of protective films used, the haze values ​​of the protective films used, the surface shapes of the protective films used, the back reflectance, and the parallel line transmittance are shown in Table 2. In Table 2, “-” means that no measurement was performed.

[0187] [Table 2]

[0188]

[0189] As shown in Table 2, in Manufacturing Examples 1 to 3, the internal haze value of the protective film is 4.0% or less. In Manufacturing Examples 1 to 3, the surface haze value of the back surface of the protective film is 6.0% or more and 50.0% or less. In Manufacturing Examples 1 to 3, the root mean square slope Sdq of the back surface of the protective film is 0.10 or more and 0.50 or less.

[0190] As shown in Table 2, in Manufacturing Examples 1 to 3, the back reflectance is 0.30% or less. Therefore, in Manufacturing Examples 1 to 3, the back reflection is reduced. In Manufacturing Examples 1 to 3, the parallel line transmittance is 30.0% or more. Therefore, in Manufacturing Examples 1 to 3, the parallel line transmittance is high.

[0191] As shown in Table 2, in Comparative Examples 1 to 4, the internal haze value of the protective film was greater than 4.0%. In Comparative Example 1, the surface haze value of the back side of the protective film was greater than 50.0%. In Comparative Examples 2 to 4, the root mean square slope Sdq of the back side of the protective film was less than 0.10.

[0192] As shown in Table 2, in Comparative Manufacturing Examples 1 to 3, the back reflectance is greater than 0.30%. Therefore, in Comparative Manufacturing Examples 1 to 3, the back reflection is not reduced. In Comparative Manufacturing Examples 1, 3, and 4, the parallel line transmittance is less than 30.0%. Therefore, in Comparative Manufacturing Examples 1, 3, and 4, the parallel line transmittance is not high.

[0193] The above results show that according to the present invention, it is possible to provide a method for producing an antireflection film capable of improving the detection accuracy of reflected light and transmitted light during in-line inspection.

Claims

1. A method for manufacturing an anti-reflection film, comprising: Step S1, preparing a laminated body including a transparent film substrate and a protective film releasably attached to a first main surface side of the transparent film substrate; Step S2, forming an antireflection layer composed of two or more thin films on the second main surface side of the transparent film substrate; and Step S3, after forming at least one layer constituting the antireflection layer, irradiating the layer with visible light, and detecting reflected light and transmitted light thereof, The steps S2 and S3 are continuously performed while conveying the laminate in one direction. The internal haze value of the protective film is 4.0% or less, The surface haze value of the main surface of the protective film on the side opposite to the transparent film substrate side is 6.0% or more and 50.0% or less.

2. The method for producing an antireflection film according to claim 1, wherein: A value obtained by subtracting a surface haze value of the main surface of the protective film on the transparent film substrate side from a surface haze value of the main surface of the protective film on the opposite side to the transparent film substrate side is 5.0% or more.

3. A method for manufacturing an anti-reflection film, comprising: Step S1, preparing a laminated body including a transparent film substrate and a protective film releasably attached to a first main surface side of the transparent film substrate; Step S2, forming an antireflection layer composed of two or more thin films on the second main surface side of the transparent film substrate; and Step S3, after forming at least one layer constituting the antireflection layer, irradiating the layer with visible light, and detecting reflected light and transmitted light thereof, The steps S2 and S3 are continuously performed while conveying the laminate in one direction. The internal haze value of the protective film is 4.0% or less, The root mean square slope Sdq of the main surface of the protective film on the side opposite to the transparent film substrate side is 0.10 or more and 0.50 or less.

4. The method for producing an antireflection film according to claim 3, wherein: A value obtained by subtracting a root mean square slope Sdq of the main surface of the protective film on the transparent film substrate side from a root mean square slope Sdq of the main surface of the protective film on the opposite side to the transparent film substrate side is 0.05 or more.

5. The method for producing an antireflection film according to claim 1 or 3, wherein: In the step S2, the antireflection layer is formed by reactive sputtering.

6. The method for producing an antireflection film according to claim 1 or 3, wherein: In the step S3 , after all the layers constituting the antireflection layer are formed, the antireflection layer is irradiated with visible light, and the reflected light and the transmitted light are detected.

7. The method for producing an antireflection film according to claim 1 or 3, wherein: The film forming conditions of the antireflection layer in the step S2 are adjusted according to the detection results of the reflected light and the transmitted light in the step S3.

8. The method for producing an antireflection film according to claim 1 or 3, wherein: The method further comprises: step S4, after step S3, peeling the protective film from the transparent film substrate.

9. The method for producing an antireflection film according to claim 1 or 3, wherein: The transparent film substrate includes a transparent film and a hard coating layer provided on a first main surface side of the transparent film. In the laminated body, the protective film is bonded to the second main surface side of the transparent film.

10. The method for producing an antireflection film according to claim 1 or 3, wherein: The method further comprises: step S5 of forming a primer layer on the second main surface side of the transparent film substrate before step S2; In the step S2, the antireflection layer is formed on the main surface of the primer layer on the opposite side to the transparent film substrate side.